International Experience with Cross-border Power Trading - World Bank (Washington, DC, 2013)
The five main lessons for Southern Africa from our review of the experiencewith cross-border power trading in other regions of the work are that: Security of supply concerns need to be explicitly addressed and understood by the parties to proposed cross-border transactions. Regional entities need to be empowered to make decisions based on legally enforceable national government commitments, particularly in relation to planning, pricing, and settlement rules. Bilateral trading provides a basis for expanding trading volumes, both through constructing the physical infrastructure that future deals will use and by establishing workable legal and regulatory frameworks. Power pools will help to generate sustained increases in cross-border trading along with other regional trading arrangements, particularly in power systems with several interconnection. The substance and process of regulatory reviews in importing and exporting countries must be clear to create sufficient investment certainty.